Synteny search identifies carnivore Y chromosome for evolution of male specific genes. Issue 3 (29th May 2019) - FAN, Huizhong; HU, Yibo; SHAN, Lei; YU, Lijun; WANG, Bing; LI, Min; WU, Qi; WEI, Fuwen
Abstract: The explosive accumulation of mammalian genomes has provided a valuable resource to characterize the evolution of the Y chromosome. Unexpectedly, the Y‐chromosome sequence has been characterized in only a small handful of species, with the majority being model organisms. Thus, identification of Y‐linked scaffolds from unordered genome sequences is becoming more important. Here, we used a syntenic‐based approach to generate the scaffolds of the male‐specific region of the Y chromosome (MSY) from the genome sequence of 6 male carnivore species. Our results identified 14, 15, 9, 28, 14 and 11 Y‐linked scaffolds in polar bears, pacific walruses, red pandas, cheetahs, ferrets and tigers, covering 1.55 Mbp, 2.62 Mbp, 964 Kb, 1.75 Mb, 2.17 Mbp and 1.84 Mb MSY, respectively. All the candidate Y‐linked scaffolds in 3 selected species (red pandas, polar bears and tigers) were successfully verified using polymerase chain reaction. We re‐annotated 8 carnivore MSYs including these 6 Y‐linked scaffolds and domestic dog and cat MSY; a total of 11 orthologous genes conserved in at least 7 of the 8 carnivores were identified. These 11 Y‐linked genes have significantly higher evolutionary rates compared with their X‐linked counterparts, indicating less purifying selection for MSY genes. Taken together, our study shows that the approach of synteny search is a reliable and easily affordable strategy to identify Y‐linked scaffolds from unordered carnivore genomes and provides a preliminary evolutionary study for carnivore MSY genes.